ENSURING CHILDREN’S SAFETY AT SCHOOL: PEDAGOGICAL APPROACHES (Educator Insights: Journal of Teaching Theory and Practice, 2026)
This article explores pedagogical approaches to ensuring children’s safety in school environments. It analyzes the importance of creating a secure educational setting, the role of teachers in preventing risks, and the implementation of preventive measures within the school system. The study highlights psychological, organizational, and educational strategies aimed at protecting students from physical, emotional, and social threats. The findings emphasize that effective school safety management contributes to students’ well-being and improves the overall quality of education.